2006
DOI: 10.1017/s0952523806231079
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic glutamate receptors of amacrine cells of the mouse retina

Abstract: The mammalian retina contains approximately 30 different morphological types of amacrine cells, receiving glutamatergic input from bipolar cells. In this study, we combined electrophysiological and pharmacological techniques in order to study the glutamate receptors expressed by different types of amacrine cells. Whole-cell currents were recorded from amacrine cells in vertical slices of the mouse retina. During the recordings the cells were filled with Lucifer Yellow0Neurobiotin allowing classification as wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 63 publications
1
18
0
Order By: Relevance
“…Amacrine cells receive glutamatergic inputs from bipolar cells and express various subtypes of glutamate receptors (Dixon and Copenhagen, 1992; Euler et al, 1996; Dumitrescu et al, 2006). GABAergic A17 amacrine cells receive excitatory input via CP-AMPARs (Chavez et al, 2006), but glycinergic amacrine cells that contact RBCs are driven by NMDA and Ca 2+ -impermeable AMPARs (Chavez and Diamond, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Amacrine cells receive glutamatergic inputs from bipolar cells and express various subtypes of glutamate receptors (Dixon and Copenhagen, 1992; Euler et al, 1996; Dumitrescu et al, 2006). GABAergic A17 amacrine cells receive excitatory input via CP-AMPARs (Chavez et al, 2006), but glycinergic amacrine cells that contact RBCs are driven by NMDA and Ca 2+ -impermeable AMPARs (Chavez and Diamond, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…In the rabbit retina, AII ACs also contributed most to the glycinergic AC response (Marc, 1999a). Dumitrescu et al (2006) showed that 77% of mice AII ACs possessed AMPA- and KA-responsive glutamate receptors but AII ACs did not express KA-responsive glutamate receptors exclusively. Electrophysical recordings from the rat and rabbit retina also indicate that AII ACs only possess functional AMPA receptors (Morkve et al, 2002; Veruki et al, 2003; Zhou and Dacheux, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In rat retina, amacrine cells receive excitatory input from bipolar cell terminals at iGluR synapses but different amacrine cell subsets express different compositions of iGluR (Nivison-Smith et al, 2013). Recordings in mouse retina have revealed that the majority of amacrine cells show both AMPA and Kainate receptor-mediated responses, with a small fraction showing only AMPA or only Kainate-mediated responses (Dumitrescu et al, 2006). …”
Section: Synapse Structure and Connectivity Of Retinal Neuronsmentioning
confidence: 99%